(untitled) (Archive of Conferences, 2021)
Over the last 10 years, the agrolandshaft has been polluted with various harmful substances due to anthropogenic factors. These include man-made radionuclides (cesium - 137, strontium - 90), heavy metals (mercury, lead, cadmium, fluorine, chromium, beryllium, aluminum, arsenic, etc.), as well as residual pesticides. These harmful substances are absorbed by plants and accumulate in vegetables. When food is fed disproportionately with mineral fertilizers and in the process of protein synthesis, unfavorable conditions occur, resulting in the formation of toxic amino acids, nitrates and nitrites, which are among the harmful substances. Toxic contaminants in products must be controlled by health authorities. The allowable saturation level is determined for each crop, and when their amount increases, the product cannot be consumed. Gastrointestinal and many other diseases can develop if the composition of food does not meet sanitary and hygienic requirements. As a result of the development of agro-industry, as a result of excessive and irregular application of nitrogen fertilizers, the amount of nitrate in fruits and vegetables is increasing. The effects of nitrates on the body have been identified and it has been found that nitrates consumed on a daily basis are important in maintaining our health.